2023
DOI: 10.3390/jzbg4010021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Failure on California Sea Lion (Zalophus californianus) Gameplay Strategies and Interest in a Cognitive Task: Implications for Cognitive Enrichment in Pinnipeds

Abstract: Cognitive enrichment for professionally managed species has become more prevalent in recent years in both zoological and research settings and has been encouraged as a means of welfare enhancement. However, the task’s difficulty must be specifically tailored as it can impact the successful nature of the sessions, as tasks that are too simple or difficult may not be perceived as enriching by the animals. While pinnipeds are common in zoos, aquariums, and research facilities, few studies have explored the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…For example, simply watching videos on these screens would not count as a cognitive challenge, but doing the initial cognitive work of learning how to interface with the system and select particular videos would. Some examples of virtual puzzles that have been used with marine mammals to date have included the following: learning how to maneuver a cursor to contact a target on the screen [ 123 ], tracking and touching moving images [ 124 ], visual match-to-sample [ 125 ], learning to match visual stimuli to associated auditory stimuli [ 56 ], and using echolocation to draw [ 126 ].…”
Section: Providing Cognitive Challenges To Marine Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, simply watching videos on these screens would not count as a cognitive challenge, but doing the initial cognitive work of learning how to interface with the system and select particular videos would. Some examples of virtual puzzles that have been used with marine mammals to date have included the following: learning how to maneuver a cursor to contact a target on the screen [ 123 ], tracking and touching moving images [ 124 ], visual match-to-sample [ 125 ], learning to match visual stimuli to associated auditory stimuli [ 56 ], and using echolocation to draw [ 126 ].…”
Section: Providing Cognitive Challenges To Marine Mammalsmentioning
confidence: 99%
“…All of the groups working with dolphins have placed the computer outside of an underwater window, and then either projected infrared light beams in front of the window, allowing dolphins to use their rostrums to interact with the computer like a touch screen [ 56 , 128 ]; or utilized an array of hydrophones in front of the window that allowed the dolphins to use their echolocation like a computer mouse [ 126 ]. The group working with sea lions placed the computer and its controls on land, and used buttons that the sea lion could press with their snout to move a cursor up, down, left, or right [ 123 , 125 ].…”
Section: Providing Cognitive Challenges To Marine Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some carnivores have shown high capability for these tasks [ 41 , 42 ], one cannot help but note the extent to which these types of interactions seem to be tailored to the primate hand and the types of physical interactions it allows. On a conceptually similar note, there is an increased interest in screen-based interactive “games” for primate enrichment [ 43 ], and this approach has recently been used very effectively with sea lions as well [ 44 ]. Clearly, these types of interventions have potential benefits for any vertebrate, inviting novel problem-solving behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term health benefits of specific enrichment approaches with animals are hard to measure, always being multi-factorial. We do have some evidence that sea lions tend to be remarkably persistent when faced with difficult cognitive challenges [ 5 ], and the innovative computer-based enrichment study discussed above [ 44 ] found that cognitive challenge was no deterrent to sea lions engaging with a device. There is evidence in bears, another canid carnivore, of “contrafreeloading” behavior [ 77 ], that is, choosing to engage in operant behavior to obtain food when other food is freely available [ 78 ], and we have seen similar behavior in captive sea lions.…”
Section: Introductionmentioning
confidence: 99%